Continuous positive airway pressure improves sleepiness but not calculated vascular risk in patients with minimally symptomatic obstructive sleep apnoea: the MOSAIC randomised controlled trial. - Craig, SE; Kohler, M; Nicoll, D; Bratton, D; Nunn, A; Davies, R; Stradling, J (2012)
Continuous positive airway pressure (CPAP) for symptomatic obstructive sleep apnoea (OSA) improves sleepiness and reduces vascular risk, but such treatment for the more prevalent, minimally symptomatic disease is contentious.